Incorporation of Heterocycles into the Backbone of Peptoids to Generate Diverse Peptoid-Inspired One Bead One Compound Libraries - Aditya, Animesh (2012)
Combinatorial libraries of peptoids (oligo-N-substituted glycines) have proven to be useful sources of protein ligands. Each unit of the peptoid oligomer is derived from 2-haloacetic acid and a primary amine. In order to increase the chemical diversity available in peptoid libraries, we demonstrate here that heterocyclic halomethyl carboxylic acids can be employed as backbone building blocks in the synthesis of peptoid-based oligomers. Optimized conditions are reported that allow the creation of large, high quality combinatorial libraries containing these units.